Analisis Belanja Daerah, Studi Kasus: Pemerintah Kabupaten Seram Bagian Barat - Shella Kriekhoff; Elisabeth Riupassa (Jurnal Administrasi Terapan, 2024)
Spending is a routine government activity that is prone to leakage and inefficiency if there is no proper planning, supervision and control, therefore spending analysis must be carried out as a basis for evaluation, improvement, and correction in the future. Regional Spending of West Seram Regency during 2020-2023 has tended to decrease in terms of spending budget. This study aims to determine the performance of the West Seram Regency Government in managing its spending budget. This quantitative descriptive study uses quantitative data in the form of Government Expenditure Realization Data of West Seram Regency during 2020-2023. The data collection technique in this study is the documentation method. The data is then processed using spending growth analysis and spending harmony analysis. The Growth Analysis results show that the shows that the spending growth ratio of the West Seram Regency Government has a negative growth tendency, meaning that from year to year the amount of spending has decreased. The Harmony Analysis shows that the pattern and orientation of West Seram Regency Government spending is mostly used for employee spending, goods and services spending, Capital Expenditure, and Financial Assistance Spending. This is in line with the results of the analysis of direct and indirect spending, with almost the majority being used for indirect spending. Keywords: spending analysis, growth ratio, spending harmony ratio.